Gut Microbiota–Driven Modulation of Host Immune Responses in Severe Infections: Mechanistic Insights and Translational Implications - Fatima Bello; Chinedu Okafor (Journal of Society Medicine, 2026)
Introduction: Severe infections, particularly sepsis and ICU-acquired infections, remain leading causes of global morbidity and mortality, primarily driven by dysregulated host immune responses. Increasing evidence positions the gut microbiota as a critical regulator of systemic immunity through bidirectional host–microbiome interactions, functioning not merely as a passive microbial reservoir but also as an active determinant of disease progression and clinical outcomes. Methods: A structured narrative synthesis was conducted using literature retrieved from PubMed, Embase, and Cochrane Library. Priority was given to high-quality randomized controlled trials, large observational cohorts, and mechanistic preclinical studies published within the past 10–15 years. Evidence was systematically appraised using standardized risk-of-bias frameworks, including Cochrane tools, and integrated into a translational model linking microbiome alterations with host immune dynamics. Results: Severe infections were consistently associated with rapid-onset gut dysbiosis, characterized by reduced microbial diversity and expansion of opportunistic pathogens. Five principal mechanistic domains were identified: immune system modulation, disruption of epithelial barrier integrity, altered microbial metabolite signaling, systemic microbial translocation, and antibiotic-induced ecological imbalance. Although observational data demonstrate strong associations between dysbiosis and adverse outcomes, interventional studies targeting the microbiome have reported heterogeneous efficacy, reflecting the underlying biological complexity and current therapeutic limitations. Conclusion: Gut microbiotas represent a dynamic and potentially modifiable regulator of host immune responses during severe infections. Future research should emphasize causal inference, precision microbiome-based interventions, and the integration of multi-omics approaches to develop mechanism-based therapeutic strategies and clinically actionable biomarkers to improve outcomes in critically ill patients.